VERNACULARIZATION IN MALAYSIAN TAFSIR: A STUDY OF TAFSIR NUR AL-IHSAN BY MUHAMMAD SA'ID AL-KEDAHI - Nuryatul Choiroh, Wahyuni (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2024)
This article discusses vernacularization in Malay-Language Tafsir by examining Tafsir Nur al-Ihsan by Syaikh Muhammad Sa'id al-Qadhi al-Kedahi as an analytical study. This oldest tafsir was written in 1344H/1926M during the reign of the 21st Sultan of Kedah by a Qadhi in Kedah Malaysia, as well as the first Malaysian mufassir who interpreted the Qur'an in Javanese with Arabic alphabet letters. This research focuses on three main problems: how vernacularization is applied in the book of Tafsir Nur al-Ihsan in the linguistic, writing, and interpretation aspects. Through the theory of vernacularization, this research explains the implementation of vernacularization related to the phenomenon and the facts of the text that developed in the book of Tafsir Nur al-Ihsan. By using a qualitative approach through the literature study method, the results of this study show that; First, vernacularization in the linguistic aspect through the use of local languages commonly used by the local community in the use of the word "sembahyang" and the designation "lembu" for naming surah al-Baqarah. Second is vernacularization in Malay writing using the Arabic-Jawi script (pegon). Third, vernacularization is found in the interpretation of QS. al-Maidah verse 38 and QS. Al-Baqarah verse 17, which dominantly reflects aspects of locality such as the expression, morality, and character of the Malaysian Muslim community, as well as the lives and habits of Malaysian Muslims, especially in the Kedah area.